Analysis of Trauma in Luna using Performativity and Gender Dysphoria - Joseph, Anns Mary (SMART MOVES JOURNAL IJELLH, 2019)
Gender is culturally constructed and the concept of gender varies from one culture to another. It is not natural but a performance, a role-play. The paper “Analysis of Trauma in Luna using Performativity and Gender Dysphoria,” depicts the plight of Liam-an attractive senior in high school who is a transgender-through the eyes of his sister, Regan. The novel traces Liam’s discovery of his true self-Luna, who can only reveal herself at night. Liam feels that he is a caricature, a puppet that lives up to the expectations and norms of the society, so much so that, he feels depressed and has suicidal tendencies; his body betrays him, and hinders him from his true identity, which creates trauma. He finally resolves to transition and transform into Luna, akin to a butterfly. Regardless of the disagreeable reception from his society, he endeavours to embrace his hidden self and sexuality, with the support of Regan. The general attitude of the society is still far from accepting the Queer community, even though the Supreme Court decriminalized Section 377 of the IPC; in such a scenario, the paper “Analysis of Trauma in Luna using Performativity and Gender Dysphoria,” attempts to depict that there is no “absolute” sexuality but sexual fluidity.